2008
DOI: 10.1007/s11661-008-9668-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Tensioning of High-Strength Aluminum Alloy Friction Stir Welds

Abstract: The extent to which in-situ global mechanical tensioning (GMT) can be used to modify the residual stress state in friction stir (FS) welds is investigated in this article. Residual stress distributions have been determined by synchrotron X-ray and neutron diffraction for four sets of FS welds in high-strength AA7449-W51 and lithium containing AA2199-T8 aerospace aluminum alloys subjected to a systematic range of GMT levels. For the cases studied, the results indicate that the level of residual stresses present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Depending on the longitudinal tensioning load used, GMT can greatly reduce residual stresses at the weld line, or even introduce compressive stresses in this region [145,146,147,148], see Figure 15b. For welds in 2000-series aluminium alloy, the magnitude of tensioning stress that must be applied during welding to reduce the longitudinal residual stress to approximately zero, has been reported as 25-40% of the room temperature yield stress of the parent material [146,148].…”
Section: Global Mechanical Tensioningmentioning
confidence: 99%
“…Depending on the longitudinal tensioning load used, GMT can greatly reduce residual stresses at the weld line, or even introduce compressive stresses in this region [145,146,147,148], see Figure 15b. For welds in 2000-series aluminium alloy, the magnitude of tensioning stress that must be applied during welding to reduce the longitudinal residual stress to approximately zero, has been reported as 25-40% of the room temperature yield stress of the parent material [146,148].…”
Section: Global Mechanical Tensioningmentioning
confidence: 99%
“…It is also revealed by Hatamleh et al [9] that the maximum extent and location of the RS is dependent to the fixture support. Furthermore, Altenkirch et al [10,11] showed that global tensioning can decrease the RS and a reverse linear relationship holds between the RS and the forces applied on thin plates.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of FSW process, the residual stresses have been experimentally obtained by measuring in longitudinal and transverse states through destructive methods [12] and nondestructive methods such as ultrasonic as well as X-ray diffraction [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…They have concluded that such location is within the thermo-mechanically affected zone (TMAZ). Furthermore, Altenkirch et al [18,19] have demonstrated that global tensioning is required to reduce the residual stress and a reverse linear relationship holds between the residual stress and the applied force in the case of thin sheets.…”
Section: Introductionmentioning
confidence: 99%